Ayurvedic Management of Ardhavbhedaka(Migraine)-A Case Study - Singh, Chandra Shekhar; Chaturvedi, Uttara Kumar (International Research Journal of Ayurveda & Yoga, 2022)
Migraine is a frequent brain illness that can be debilitating. Chronic migraine (CM) is defined as 15 headache days per month, whereas episodic migraine (EM) is defined as 15 headache days per month. According to the World Health Organization (WHO), 3000 migraine attacks occur daily for every million people. When the quality of life is seriously impacted by migraine, prophylactic medication treatment should be explored. Migraine can be clinically correlated with Ardhavbhedaka. In present case study the patient of Ardhavabhedaka was treated with Sarvang Abhyang, Swedan, Mustyadi Yapana Basti and Shaman Chikitsa. We selected the drugs for shaman Chikitsa Shudh Tankan Bhasm, Sphatika Bhasma, Lodhra Churna, Nagkesar Churmna, Lodhra Asaav ,Tab Vingrai, Syp M Shankhpuspi and Smritisagar ras were used. There was a significant reduction in symptoms in the patient. The patient experienced complete relief from migraine symptoms after undergoing all of the aforementioned treatments. After 3 months, the patient was followed up on, and there had been no recurrence of symptoms or ill effects from the therapy.